2022
DOI: 10.3390/math10050767
|View full text |Cite
|
Sign up to set email alerts
|

Existence and Uniqueness Results for Fractional (p, q)-Difference Equations with Separated Boundary Conditions

Abstract: In this paper, we study the existence of solutions to a fractional (p, q)-difference equation equipped with separate local boundary value conditions. The uniqueness of solutions is established by means of Banach’s contraction mapping principle, while the existence results of solutions are obtained by applying Krasnoselskii’s fixed-point theorem and the Leary–Schauder alternative. Some examples illustrating the main results are also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…Then, By (27), we have L ≈ 0.0009667625 < 1. Hence, Theorem 7 concludes that the generalized sequential (p; q)-difference Navier problem (33) has at least one solution on I 0.25 (0.5;0.45) .…”
Section: Now By (26) We May Writementioning
confidence: 83%
See 1 more Smart Citation
“…Then, By (27), we have L ≈ 0.0009667625 < 1. Hence, Theorem 7 concludes that the generalized sequential (p; q)-difference Navier problem (33) has at least one solution on I 0.25 (0.5;0.45) .…”
Section: Now By (26) We May Writementioning
confidence: 83%
“…so that D (p;q) and c D r (p;q) are the 1st order and r-th order (p; q)-difference and (p; q)derivative of the Caputo-like type, respectively, and E ∈ C([0, T p r ] × R, R). Once again in 2022, the same authors [33] defined a new function E ∈ C([0, T] × R, R) to simplify the domain of it, and to study the existence theorems, modeled the r-th order (p; q)-difference problem of the Caputo-like type as…”
Section: Introductionmentioning
confidence: 99%
“…Then, taking into account some fundamental fixed point theorems such as the Banach contraction principle, the Boyd-Wong fixed point theorem, and the Leray-Schauder nonlinear alternative, they provided the existence (uniqueness within some cases) of solutions to this problem under some certain conditions on f and constants. A variety of new results on (p, q)-difference equations via fixed point theory can be found in [18,19,[29][30][31]34]. Now, let us review basic definitions and theorems about (p, q)-calculus, which are found in [36].…”
Section: Introductionmentioning
confidence: 99%